The Role of Geographic Information Systems (GIS) in Designing Maps of Industrial Land Use Change in the City of Hillah - برهي ميعاد عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The study seeks to demonstrate the role of modern technologies, including geographic information systems (GIS), in constructing thematic maps of industrial land uses using the Arc Map program. A special database was created to prepare, analyze, and process geographic data on industrial land uses. The study focuses on industrial activity in Babil Governorate and includes large, medium, and small-sized establishments, according to the classification adopted by the Central Bureau of Industrial Statistics. It is self-evident that every city must provide jobs for its residents or for residents of the surrounding areas (its regions or hinterland). These jobs occupy their spatial scope in the form of uses that share the city’s built-up land, including industrial uses, as well as other uses such as administrative, educational, and recreational uses. The city of Hillah is one of the important cities and a major administrative center in Babil Governorate. The researcher sought to study industrial land uses in this city, identifying the areas occupied by industrial types and the spatial distribution of industrial use patterns for the years 1997 and 2023. The spatial distribution of industrial use patterns was then determined using land use maps. If the research dealt with several axes, including first the theoretical framework, second (the role of geographic information systems in preparing the database for designing land use maps), third (the spatial distribution of industrial use patterns for the year 1997), fourth (the spatial distribution of industrial use patterns for the year 2023), fifth (the spatial distribution of the spatial change in industrial use in the city of Hillah), the research ended in its entirety with conclusions that are considered the final result of this study